2013
DOI: 10.1016/j.atherosclerosis.2013.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Association between carotid intima-media thickness and retinal arteriolar and venular diameter in patients with hypertension: A cross-sectional study

Abstract: In patients with hypertension, carotid intima-media thickness, a marker of macrovascular damage, is significantly and independently associated with microvascular damage, determined by retinal arteriolar and venular calibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Two studies reported a weak association between narrower arteriolar caliber and higher CIMT (standardized β = −0.06; Table ), while the other four studies did not show a significant association. However, in the only study with cardiometabolic patients, this association was not replicated …”
Section: Resultsmentioning
confidence: 91%
“…Two studies reported a weak association between narrower arteriolar caliber and higher CIMT (standardized β = −0.06; Table ), while the other four studies did not show a significant association. However, in the only study with cardiometabolic patients, this association was not replicated …”
Section: Resultsmentioning
confidence: 91%
“…First, an Australian study showed that moderate/high yoghurt consumption, but not total dairy or milk intake, was associated with significantly lower common carotid artery intima-media thickness (CCA-IMT), a predictor of coronary events [27]. Torres et al [28] reported that CCA-IMT was a significant predictor of both retinal arteriolar and venular diameters, demonstrating that vascular damage occurs in parallel in large arteries and small vessels. Hence, yoghurt consumption could have beneficial effects on the retinal microcirculation by lowering CCA-IMT.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, the associations between central retinal arteriolar equivalent (CRAE) and many cardiovascular risk factors have been demonstrated [1][5]. The American Heart Association estimates that more than 1 in 3 adults Americans have one or more types of cardiovascular disease [6].…”
Section: Introductionmentioning
confidence: 99%